2020
DOI: 10.3389/fimmu.2020.531785
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 (IL-2) Interacts With IL-2 Receptor Beta (IL-2Rβ): Its Potential to Enhance the Proliferation of CD4+ T Lymphocytes in Flounder (Paralichthys olivaceus)

Abstract: Interleukin-2 (IL-2) Interacts With IL-2 Receptor Beta (IL-2Rβ): Its Potential to Enhance the Proliferation of CD4+ T Lymphocytes in Flounder (Paralichthys olivaceus).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…At the same time, T-bet was mainly expressed in CD4 + helper T cells, which explains the proliferation of CD4-1 + and CD4-2 + T cells in flounder after IFN-γ stimulation. In our previous study, we found that IL-2 was able to induce proliferation of CD4 + T cells through specific binding to its receptor IL-2R, and T-bet gene expression was found to be upregulated after stimulation with IL-2 ( 32 ), which is consistent with the results of the present study, where IL-2 was able to induce an increase in T-bet + cells and CD4 + T cell subpopulations. In the previously study, CD4-2 + T cells, rather than CD4-1 + T cells have a main role in Th1 immune responses, collaborating with CD8α and CD8β positive cells in flounder ( 46 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the same time, T-bet was mainly expressed in CD4 + helper T cells, which explains the proliferation of CD4-1 + and CD4-2 + T cells in flounder after IFN-γ stimulation. In our previous study, we found that IL-2 was able to induce proliferation of CD4 + T cells through specific binding to its receptor IL-2R, and T-bet gene expression was found to be upregulated after stimulation with IL-2 ( 32 ), which is consistent with the results of the present study, where IL-2 was able to induce an increase in T-bet + cells and CD4 + T cell subpopulations. In the previously study, CD4-2 + T cells, rather than CD4-1 + T cells have a main role in Th1 immune responses, collaborating with CD8α and CD8β positive cells in flounder ( 46 ).…”
Section: Discussionsupporting
confidence: 92%
“…Lymphocytes were isolated from 18 flounder head kidney with aseptic technique in each group, and 72 (a half of fish used for flow cytometry, and a half of fish used for cell sorting) flounder were totally used in this experiment. Then, the cells were transferred to 24-well culture plates (800 μl/well) to ensure 5 × 10 6 cells per well, and cultured in L-15 medium with 10% fetal calf serum and penicillin/streptomycin supplemented with IFN-γ, IL-2, and IL-6 (100 ng/well) ( 32 ). PBS was added to the cells as control.…”
Section: Methodsmentioning
confidence: 99%
“…Then, cells were washed three times in L-15 medium with 10% FBS and adjusted to 5 × 10 6 cells/ml and placed into a 12-well culture plate (2 ml/well) cultured in L-15 medium with 10% FBS. Stimulated cells were treated with 5 μg/ml PHA (Sigma) or 5 μg/ml PHA + 0.5 μg/ml anti-CD28 Abs ( 40 ). Unstimulated cells were treated with an equal amount of sterile PBS medium as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse polyclonal antibodies against flounder IL-2 (diluted at 1:500) and monoclonal antibodies against flounder IgM (diluted at 1:1,000), CD4-1 (diluted at 1:1,000), and CD4-2 (diluted at 1:1,000) were previously produced in our laboratory (38)(39)(40). The secondary antibodies included DyLight 488 (Abbkine; diluted at 1:1,000) rabbit or mouse IgG, DyLight 649 (Abbkine; diluted at 1:1,000) rabbit or mouse IgG, alkaline phosphatase (AP)-conjugated goat anti-rabbit IgG (H + L) (Abbkine; diluted at 1:5,000), and HRP-conjugated goat anti-mouse IgG (Abbkine; diluted at 1:5,000).…”
Section: Animals Cells and Antibodiesmentioning
confidence: 99%
“…Currently, the term "cytokine" encompasses many types of proteins, including interleukins, chemokines, and the tumor necrosis factor (TNF) family. Interleukins mediate interactions between immune cells and are able to promote cell proliferation, differentiation, and functional activation [8][9][10][11]. Chemokines induce cell migration and activation by binding to specific G-protein-coupled cell surface receptors on target cells, such as neutrophils, monocytes, and lymphocytes, which play a pivotal role in host immune defense [12][13][14].…”
Section: Introductionmentioning
confidence: 99%